Ecotoxicity of isosorbide acrylate and methacrylate monomers and corresponding polymers. Issue 4 (7th February 2023) - Ismagilova, Alina; Matt, Livia; Jannasch, Patric; Kisand, Veljo; Vares, Lauri
Abstract : Environmental impact of isosorbide-based monomers and polymers have been evaluated towards bacteria, plants and invertebrates. Isosorbide acrylates show toxicity towards higher organisms while other tested mono- and polymeric compounds are harmless. Abstract : Isosorbide is a well-investigated and accessible biomass-derived compound that has found wide use in medicine, cosmetics, and materials science. The efforts to employ this rigid bicyclic diol as a sustainable building block in high-performance biobased plastics for, e.g., the engineering, coating, and packaging sectors have grown sharply in recent years. Due to the biomass origin, there is an implicit assumption of a low toxicity and an environmentally benign nature of isosorbide-derived plastics. In the present work, the ecotoxicity of isosorbide acrylate and methacrylate monomers and the corresponding poly(meth)acrylates, as well as industrially produced latexes from these monomers, were evaluated towards bacteria ( Escherichia coli, Aliivibrio fischeri ), vascular plants ( Spirodela polyrhiza ) and invertebrates ( Thamnocephalus platyurus ) using widely acknowledged test assays. The measured half maximal effective concentration (EC50 ) values indicate that the chemically reactive isosorbide acrylate monomers are toxic towards higher multicellular organisms ( S. polyrhiza and T. platyurus, EC50 ∼ 9 mg L −1 ) and moderately toxic towards bacteria ( E. coli ), whereas the corresponding methacrylate monomers can be considered as practically harmless or harmless on the same test assays. Corresponding isosorbide polyacrylate and polymethacrylate polymers are harmless towards the tested organisms (EC50 > 1000 mg L −1 ), except towards E. coli, where two polymers are classified as practically harmless (EC50 = 374 and 514 mg L −1 ). Moreover, industrially produced isosorbide methacrylate derived latexes can be classified as harmless based on this study.